Anti-Niemann Pick C1 Single-Stranded Oligonucleotides with Locked Nucleic Acids Potently Reduce Ebola Virus Infection In Vitro - Anne Sadewasser; Erik Dietzel; Sven Michel; Michael Klüver; Markus Helfer; Tamara Thelemann; Richard Klar; Markus Eickmann; Stephan Becker; Frank Jaschinski (Elsevier, 2019)
Ebola virus is the causative agent of Ebola virus disease, a severe, often fatal illness in humans. So far, there are no US Food and Drug Administration (FDA)-approved therapeutics directed against Ebola virus. Here, we selected the host factor Niemann-Pick C1 (NPC1), which has been shown to be essential for Ebola virus entry into host cytoplasm, as a therapeutic target for suppression by locked nucleic acid-modified antisense oligonucleotides. Screening of antisense oligonucleotides in human and murine cell lines led to identification of candidates with up to 94% knockdown efficiency and 50% inhibitory concentration (IC50) values in the submicromolar range. Selected candidate oligonucleotides led to efficient NPC1 protein knockdown in vitro without alteration of cell viability. Furthermore, they did not have immune stimulatory activity in cell-based assays. Treatment of Ebola-virus-infected HeLa cells with the most promising candidates resulted in significant (>99%) virus titer reduction, indicating that antisense oligonucleotides against NPC1 are a promising therapeutic approach for treatment of Ebola virus infection. Keywords: Ebola virus, antisense oligonucleotide, NPC1, LNA